Application of Energy-saving and Emission-reducing Technology in Street Lights in Citizens' Exercise Areas. Issue 4 (May 2020) - Yu, Tianbo; Ji, Lei; Liu, Wei
Abstract: At this stage, research and development and use of energy-saving and environmental protection technologies are increasingly widespread. Especially in recent years, China has put forward a sustainable development strategy. The author has carried out a retrofit study on the urban street lighting system and transformed the urban lighting system. This paper proposes to build a professional and energy-efficient urban street lighting that meets the standards of energy conservation and environmental protection System, and specifically proposed a new type of lighting system, which can effectively reduce the energy consumption of power supply, effectively provide power supply when suppressing reactive power, and rebuild the circuit, in the street light After the system was applied to the residents' sports area, we found that it has the advantages of low running cost, easy expansion and convenient maintenance.